Shared Control Schemes for Middle Ear Surgery - So, Jae-Hun; Sobucki, Stéphane; Szewczyk, Jérôme; Marturi, Naresh; Tamadazte, Brahim (Frontiers in Robotics and AI, 2022)
This paper deals with the control of a redundant and collaborative robotic arm in order to achieve peg-in-hole insertion tasks. The proposed controller combines force or position and vision feedback in the same control scheme. Two classical control modes were first investigated; the first one consists of a position-based end-frame tele-operation controller and the second of a comanipulation controller. Based on these two well-established control architectures, we then proposed an original combination of visual feedback and position/force-based inputs in the same control scheme. Actually, instead of equally controlling the whole set of degrees of freedom (DoF) like in the classical controllers for the achievement of the peg-in-hole insertion tasks, the proposed shared controllers allow separating the linear DOF which are controlled in tele-operation (respectively, comanipulation), while the rotational ones are managed simultaneously by a vision-based control law. One major advantage of combining position or force and visual feedback in the same control architecture, is the ability to perform more complex positioning tasks such as accurate assembly or insertion tasks. In fact, these complex tasks can be simplified for the operator to basic translations in the space (carried out in tele-operation or comanipulation) while the vision-based method automatically and simultaneously controls the remaining angular DOF. The proposed methods were successfully validated and compared using a 7~DoF cobotic arm equipped with a force/torque sensor and a camera attached in an eye-in-hand configuration. The obtained results in terms of accuracy, ergonomics and rapidity are discussed in this paper.